Fire and Emergency Services Administration : management and leadership practices - Smeby, L. Charles (Burlington, Massachusetts : Jones & Bartlett Learning, 2022)
"This book is designed to be a progressive primer for students who want more knowledge about fire and emergency services administration. The book demonstrates the importance of the following skills, necessary to manage and lead a fire and emergency services department through the challenges and changes of the 21st century: Persuasion and influence, accountable budgeting, anticipation of challenges and the need for change, and using specific management tools for analyzing and solving problems. A central part of the book focuses on how the leadership of a fire and emergency services department develops internal and external cooperation to create a coordinated approach to achieving the department's mission"--
Includes bibliographical references and index.
Keywords: Fire departments -- Management; Personnel management; Leadership